Pengembangan video bimbingan nuansa kalindaqdaq untuk meningkatkan konsep diri siswa MTs - Zulfianah Sunusi (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The research is analyzing the video development of counseling using Kalindaqdaq nuance to improve the self concept of the students in MTs DDI Kec. Campalagian Kab. Polman. The research problem consists of (1) What is the descriptions of the self concept of the students in MTs DDI Kec. Campalagian Kab. Polman? (2) How to produce video of counseling with Kalindaqdaq nuance that is acceptable (utility, feasibility, and accuracy)? (3) Does the video of counseling using Kalindaqdaq nuance give effect/influrnce t o increase the self concept of  the students in MTs DDI Kec. Campalagian Kab. Polman? The objectives of the research are  (1) to know the description of the self conceptthe students in MTs DDI Kec. Campalagian Kab. Polman. (2) To create  a video of counseling with Kalindaqdaq nuance which is acceptable  (utuluty,  feasibiliy), AND accuratiom. (3) to know the effect of the video of Kalindaqdaq nuance to enhance the self-concept of the students in MTs DDI Kec. Campalagian Kab. Polman.